The Synthetic Myeloperoxidase Inhibitor AZD3241 Ameliorates Dextran Sodium Sulfate Stimulated Experimental Colitis - Ahmad, Gulfam; Chami, Belal; Liu, Yuyang; Schroder, Angie L.; San Gabriel, Patrick T.; Gao, Antony; Fong, Genevieve; Wang, XiaoSuo; Witting, Paul K. (Frontiers in Pharmacology, 2020)
Chronic inflammatory bowel disease (IBD) is a condition with multifactorial pathophysiology. To date, there is no permanent cure and the disease is primarily managed by immunosuppressive drugs; long-term use promotes serious side effects including increased risk malignancies. The current study aimed to target neutrophil-myeloperoxidase, a key contributor to the pathogenesis of IBD, through the use of AZD3241that inhibits extracellular myeloperoxidase. Experimental colitis was induced in C57BL/6 male mice by 2% dextran sodium sulphate in drinking water ad libitum over 9 days. Mice received either normal drinking water and peanut butter (control), 2% DSS in drinking water and peanut butter or 2% DSS in drinking water and AZD3241 (30mg/kg) dispersed in peanut butter daily for 9 days. Administered AZD3241 attenuated body weight loss (10% p<0.05) and improved clinical score (9 fold p<0.05; a score comprising the time-dependent assessment of stool consistency and extent of rectal bleeding), loss of colonic crypts (p<0.001), preserved surface epithelium (p<0.001) and enhanced expression of the transcription factor Nrf-2 (regulator of antioxidants) and enhanced expression of the downstream antioxidant response element haeoxygenase-1 (HO-1) in the colon tissue. Also, the concentration of fecal haemoglobin and the myeloperoxidase specific oxidative damage biomarker 3-chlorotyrosine in the colon were significantly decreased in the presence of AZD3241. This latter result was consistent with AZD3241 inhibiting MPO activity in vitro. Overall, AZD3241 ameliorated the course and severity of experimental colitis through ameliorating MPO derived tissue damage and could be considered a potential therapeutic option, subject to further validation in chronic IBD models.